Alteración dentofacial de una paciente clase III y su manejo ortodóncico quirúrgico : reporte de caso clínico (2005)
ABSTRACT: A clinical case report of a fifteen year old female with an Angle class III malocclusion and with maxillary deficiency and mandibular prognathism is presented. The patient initially consulte